DESCRIPTION OF BILIRUBIN CONDITION CHECKING ON ALCOHOL CONSUMER IN EAST POHUWATO VILLAGE, POHUWATO DISTRICT - Fransiska Polangitan; Dede Sutriono; Natan Pasiga (Journal of Health, Technology and Science (JHTS), 2021)
Based on 2014 WHO data, 61.7% of the world's population has consumed alcohol for more than 12 months which has caused around 3.3 million deaths or 5.9% of all deaths worldwide. For the 2018 RISKESDAS data in Indonesia, the first highest alcohol consumption area is North Sulawesi 16%, followed by East Nusa Tenggara 15.6, then Bali area 14%, and for Gorontalo area 11.3%. The purpose of this study was to determine the description of bilirubin levels in alcohol consumers in Pohuwato Timur Village, Pohuwato Regency including the length of time of consumption, age, types of drinks frequently consumed, frequency of alcohol consumption, and frequency of the amount of alcohol in one drink. This research uses descriptive research which is quantitative in nature. The population in the study was 55 samples with a sample size of 36 respondents who used the sampling technique, namely simple random sampling. The results showed that of the 36 respondents where the normal bilirubin levels were 14 respondents or if the percentage was 39%, while for the abnormal or high bilirubin levels there were 22 respondents or if the percentage was 61%. Based on the results obtained, it can be concluded that the results of the examination of bilirubin levels in alcohol consumers in Pohuwato Timur Village, Pohuwato Regency are more dominant with abnormal or high levels compared to normal bilirubin levels.